2019
DOI: 10.2807/1560-7917.es.2019.24.3.1800699
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of enterovirus D68 clade D1, France, August to November 2018

Abstract: We report a seasonal increase of enterovirus D68 (EV-D68) cases in France, with 54 cases detected between 19 August and 14 November 2018. Molecular typing revealed that 20 of 32 of the isolates belonged to clade D1, only sporadically detected before in France. Median age of D1-cases was 42 years, 10 developed severe respiratory signs and one had neurological complications. The 2018-D1 viruses showed a genetic divergence of 3.34 % with D1 viruses identified previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 16 publications
20
41
0
Order By: Relevance
“…Interestingly, 66% of sequences from 2017-2018 which belonged to subclade D1 were identified in adult patients with respiratory symptoms, suggesting a possible different epidemiology of this new strain. These findings had already been observed in previous studies [30].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Interestingly, 66% of sequences from 2017-2018 which belonged to subclade D1 were identified in adult patients with respiratory symptoms, suggesting a possible different epidemiology of this new strain. These findings had already been observed in previous studies [30].…”
Section: Discussionsupporting
confidence: 90%
“…The phylogenetic tree showed that most of the Spanish EV-D68 sequences detected during 2016 clustered to the recently described lineage B3 [33], while strains from 2014 and 2015 belonged to subclade B2. Similar results have been obtained with other studies [34,35], suggesting that all the 2016 outbreaks would be [28][29][30]. These findings indicate that although EV-D68 epidemics can be due to the emergence of new lineages, multiple clades have been circulating simultaneously worldwide from 2010 to the present day.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations